Coverage, efficacy or dosing interval: which factor predominantly influences the impact of routine childhood vaccination for the prevention of varicella? A model-based study for Italy - Katsiaryna Holl; Christophe Sauboin; Emanuele Amodio; Paolo Bonanni; Giovanni Gabutti (BMC, 2016)
Abstract Background Varicella is a highly infectious disease with a significant public health and economic burden, which can be prevented with childhood routine varicella vaccination. Vaccination strategies differ by country. Some factors are known to play an important role (number of doses, coverage, dosing interval, efficacy and catch-up programmes), however, their relative impact on the reduction of varicella in the population remains unclear. This paper aims to help policy makers prioritise the critical factors to achieve the most successful vaccination programme with the available budget. Methods Scenarios assessed the impact of different vaccination strategies on reduction of varicella disease in the population. A dynamic transmission model was used and adapted to fit Italian demographics and population mixing patterns. Inputs included coverage, number of doses, dosing intervals, first-dose efficacy and availability of catch-up programmes, based on strategies currently used or likely to be used in different countries. The time horizon was 30 years. Results Both one- and two-dose routine varicella vaccination strategies prevented a comparable number of varicella cases with complications, but two-doses provided broader protection due to prevention of a higher number of milder varicella cases. A catch-up programme in susceptible adolescents aged 10-14 years old reduced varicella cases by 27-43 % in older children, which are often more severe than in younger children. Coverage, for all strategies, sustained at high levels achieved the largest reduction in varicella. In general, a 20 % increase in coverage resulted in a further 27-31 % reduction in varicella cases. When high coverage is reached, the impact of dosing interval and first-dose vaccine efficacy had a relatively lower impact on disease prevention in the population. Compared to the long (11 years) dosing interval, the short (5 months) and medium (5 years) interval schedules reduced varicella cases by a further 5-13 % and 2-5 %, respectively. Similarly, a 10 % increase in first-dose efficacy (from 65 to 75 % efficacy) prevented 2-5 % more varicella cases, suggesting it is the least influential factor when considering routine varicella vaccination. Conclusions Vaccination strategies can be implemented differently in each country depending on their needs, infrastructure and healthcare budget. However, ensuring high coverage remains the critical success factor for significant prevention of varicella when introducing varicella vaccination in the national immunisation programme.